2020
DOI: 10.1155/2020/7145728
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Contrast-Enhanced Ultrasound versus Doppler Ultrasound in Grading Renal Artery Stenosis

Abstract: Objective. This study is aimed at exploring the accuracy of contrast-enhanced ultrasound (CEUS) in grading renal artery stenosis. Methods. 122 renal arteries with suspected renal artery stenosis were selected. DSA, DUS, and CEUS were performed for all patients with suspected renal artery stenosis in the research. DSA was selected as the gold standard. The sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of CEUS or Doppler ultrasound (DUS) in the diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 36 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…Authors, in a study including 120 patients with 38 stenosed renal arteries, reported surprisingly good results [38]; sensitivity, specificity, PPV, NPV and accuracy were reported as being 100%, 84%, 0%, 80% and 94%, respectively, for CDUS compared with angiography. Recently, Cui et al [39] have shown that CEUS is accurate in grading renal artery stenosis, and may represent the method of choice in diagnosing renal artery stenosis. Nevertheless, the use of CEUS in patients with renal artery stenosis is still debated and, in the near future, the application of new parametric software will allow for a quantitative analysis of contrast enhancement curves and a more accurate definition of renal perfusion.…”
Section: Renal Artery Stenosismentioning
confidence: 99%
“…Authors, in a study including 120 patients with 38 stenosed renal arteries, reported surprisingly good results [38]; sensitivity, specificity, PPV, NPV and accuracy were reported as being 100%, 84%, 0%, 80% and 94%, respectively, for CDUS compared with angiography. Recently, Cui et al [39] have shown that CEUS is accurate in grading renal artery stenosis, and may represent the method of choice in diagnosing renal artery stenosis. Nevertheless, the use of CEUS in patients with renal artery stenosis is still debated and, in the near future, the application of new parametric software will allow for a quantitative analysis of contrast enhancement curves and a more accurate definition of renal perfusion.…”
Section: Renal Artery Stenosismentioning
confidence: 99%
“…Renal cortical blood perfusion was an important imaging index that affected the prognosis of RAS patients. Feng Qichen et al ( 7 ) found that the renal filtration fraction increased significantly before stenting by using 99mTc-EC to measure the effective renal plasma flow, combined with radionuclide renal imaging to determine GFR, and calculate the renal filtration fraction (normally 18–22%). Patients with normal preoperative renal filtration scores had partially improved renal function, while those with a reduced preoperative renal filtration score had a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that age, diabetes, and severe hypertension were conventional factors for RFD in RAS patients ( 6 ). In addition, for patients with severe stenosis requiring stenting, the degree of RAS was not significantly related to the risk of RFD ( 7 , 8 ). However, with the progress of contrast-enhanced ultrasound (CEUS) and other imaging omics, renal parenchymal blood perfusion was also an important factor ( 9 ).…”
Section: Introductionmentioning
confidence: 94%
“…Contrast-enhanced US can be used to directly depict stenosis in the renal artery and poststenotic dilatation [ 23 , 66 ] ( Figure 5 ). In addition, the US signal of an involved kidney is lower than that of the other kidney in the case of unilateral RAS [ 67 ].…”
Section: Renal Artery Us: Imaging Featuresmentioning
confidence: 99%